Total Laryngectomy with Horizontal Mechanical Closure of the Pharyngoesophagectomy: Evaluation of the Effectiveness in Elderly Patients - Allegra, Eugenia; Mantia, Ignazio La; Azzolina, Alfio; Natale, Massimo De; Trapasso, Serena; Saita, Vincenzo (International Archives of Otorhinolaryngology, 2019)
Introduction The main modalities of surgical treatment for laryngeal cancer include transoral laser microsurgery (TLM), open preservation surgery, and total laryngectomy (TL). In the elderly, for the presence of comorbidities, the surgical approach more appropriate in many cases remains TL. The use of a stapler for the closure of the esophagus has been introduced to reduce surgical time and postoperative complications such as pharyngocutaneous fistula (PCF).Objective In the present study, we have evaluated the effectiveness of the use of the horizontal mechanical pharyngoesophageal closure in patients who underwent TL.Methods This nonrandomized study was performed on consecutive patients with histopathologically proven squamous cell endolaryngeal carcinoma. The TL was performed using a linear stapler to mechanically suture the pharyngotomy using the semiclosed technique.Results A total of 33 patients underwent TL, and 13 of them underwent neck dissection. A total of 15 patients (45.4%) were ≤70 years old, and 18 were > 70 years old. Analyzing the results in relation to age, patients > 70 years old showed tumors at an earlier stage than those aged ≤70 years old. Furthermore, in this group there was a greater number of patients who had comorbidities (p = 0.014). In total, we had 2 (6%) cases of PCF in 6.6% in the group ≤70 years old, and in 5.5% of the group > 70 years old (p = 1.00).Conclusions The use of the stapler for the horizontal closure of the pharyngoesophagectomy in the patients subjected to TL is proven to be useful and safe even when used in elderly patients.
Keywords: total laryngectomy; laryngeal cancer; pharyngocutaneous fistula